Inhibitory effect of chlorophyll c2 from brown algae, Sargassum horneri, on degranulation of RBL-2H3 cells - Hisashi Yoshioka; Akira Kamata; Tatsuya Konishi; Jun Takahashi; Hiroshi Oda; Tadakazu Tamai; Haruhiko Toyohara; Takuya Sugahara (Journal of Functional Foods, 2013)
The anti-allergic effect of alcohol extracts from edible seaweeds was evaluated by the degranulation of a rat basophilic leukemia cell line (RBL-2H3). Extracts prepared from the brown algae Sargassum horneri, Ecklonia cava and Ecklonia kurome, inhibited the degranulation of RBL-2H3 cells, whereas those from green algae and red algae did not. The active substance in S. horneri was purified and identified as chlorophyll c2, a major pigment in brown algae. The purified chlorophyll c2 preparation also suppressed the degranulation of RBL-2H3 cells. In contrast, chlorophyll a and b did not affect cell degranulation. Therefore, chlorophyll c2 from brown algae might be useful for the prevention or mitigation of allergic symptoms.